A method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation and its application
Through citric acid complexation and two-step high-temperature treatment technology, a copper-bismuth co-doped bamboo charcoal catalyst with high catalytic activity and structural stability was prepared, which solved the problem of difficulty in regulating catalytic activity in the prior art and significantly improved the efficiency of antibiotic wastewater treatment.
Patent Information
- Application Number
- CN202411975566.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing bamboo charcoal catalyst preparation technology cannot effectively regulate catalytic activity, and cannot build multiple catalytic activity centers on bamboo charcoal support at the same time, making it difficult to meet the higher demand for catalyst activity in modern industries.
The bamboo powder was modified by citric acid complexing by copper ion (Cu2+) and bismuth ion (Bi3+) and a copper-bismuth co-doped bamboo charcoal catalyst doped with nano Cu2O, CuO, Bi2O3, and CuBi2O4 crystal phases were prepared by two-step high-temperature treatment.
The prepared copper-bismuth co-doped bamboo charcoal catalyst has the advantages of stable structure, strong adsorption capacity and high catalytic activity. It can significantly improve the efficiency of antibiotic wastewater treatment and can completely degrade ofloxacin within 25 minutes.
Smart Images

Figure CN119386885B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation for water purification, and specifically relates to a method for preparing a copper-bismuth co-doped bamboo charcoal catalyst by citric acid complexation, and application of the copper-bismuth co-doped bamboo charcoal catalyst in treating antibiotic-contaminated wastewater. Background Art
[0002] Bamboo grows rapidly and is widely distributed in my country. It is an important biomass resource. Biochar materials have excellent adsorption properties and structural stability, and are good carriers for various catalysts. Functionalized biochar materials prepared from agricultural and forestry wastes such as bamboo have the advantages of strong adsorption capacity and stable chemical properties, and are often used for sewage purification. The cost of using bamboo charcoal catalysts for sewage treatment is often lower than that of other catalysts. At present, the modification of bamboo charcoal mostly utilizes its rich pore structure to adsorb and load catalysts, thereby achieving the functional modification of bamboo charcoal. However, the existing preparation technology cannot effectively regulate the catalytic activity, and it is impossible to simultaneously construct multiple catalytic active centers on the bamboo charcoal carrier. Therefore, the existing bamboo charcoal functionalization design and preparation method are difficult to adapt to the higher demand for catalyst activity in the modern industrial field, and a more effective solution is urgently needed to solve the above problems.
[0003] New pollutants refer to harmful chemical substances that are discharged into the environment and have characteristics such as biological toxicity, environmental persistence, and bioaccumulation, which pose a great risk to the ecological environment or human health, but for which existing management measures are insufficient. Among them, antibiotic pollution is one of the "new pollutants" that are currently widely concerned internationally. It has the characteristics of a wide range of pollution and great ecological harm. Antibiotics in the environment come from medicine, veterinary drugs and aquaculture, and destroy the balance of the ecosystem by affecting the population size of microorganisms in the environment and the population structure and nutritional mode of other organisms. In addition, antibiotics induce drug resistance in pathogenic microorganisms in the environment, causing a large number of pathogens to multiply. Antibiotics are used in large quantities in medical and health care and livestock and poultry farming, and the unused parts are released into water and soil to become one of the main pollutants. In recent years, the harm of antibiotics to the environment has received increasing attention, and how to efficiently eliminate antibiotic pollution has become a research hotspot. Among the many pollutant treatment technologies, advanced oxidation technology (AOPs) is a sewage purification technology that degrades organic pollutants in water based on the oxidation of a series of active species. It has attracted much attention due to its high efficiency, low cost and no secondary pollution. Advanced oxidation technology mainly includes Fenton oxidation (hydrogen peroxide activation), photocatalysis and Fenton-like oxidation. Pollutant oxidation degradation technology based on activated persulfate is a very promising wastewater treatment technology developed in recent years. It belongs to a type of Fenton-like oxidation reaction. Persulfate can usually be activated by light, electricity and ultrasound to produce a variety of active free radicals to oxidize and decompose pollutants. However, these technologies are hindered by high costs and equipment complexity, which limits their practical application in wastewater treatment. In recent years, some studies have shown that potassium permonosulfate (PMS) can be activated by some transition metal oxides and biochar. After activation, the peroxide bond of PMS breaks to produce sulfate radicals (SO4• - ) and singlet oxygen ( 1 O2) and other active species. These highly oxidizing active species can quickly and thoroughly oxidize and decompose the organic pollutants in the sewage. Summary of the invention
[0004] In view of the problems of low catalytic activity and high preparation cost of existing catalysts, the present invention provides a method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation. The method of the present invention treats bamboo powder with copper ions (Cu 2+ ) and bismuth ions (Bi 3+ ) modification, and then further preparing a bamboo charcoal catalyst in which nano-Cu2O, CuO, Bi2O3, and CuBi2O4 crystal phases are doped in the graphite phase after two steps of high temperature treatment. The copper-bismuth co-doped bamboo charcoal catalyst provided by the present invention has the advantages of stable structure, strong adsorption capacity, and high catalytic activity, and can significantly improve the efficiency of antibiotic-containing wastewater treatment.
[0005] The preparation method of the copper and bismuth co-doped bamboo charcoal catalyst of the present invention is as follows:
[0006] 1. Preparation of alkaline methanol-DMF solution
[0007] Methanol and DMF (N,N-dimethylformamide) are mixed in a volume ratio of 2:1 to prepare a methanol-DMF mixed solution, and NaOH is added to the methanol-DMF mixed solution to prepare a solution with a NaOH mass volume (mg / mL) concentration of 35-45%, namely, an alkaline methanol-DMF solution;
[0008] 2. Preparation of bamboo powder modified by citric acid-Cu-Bi complex
[0009] Weigh bamboo powder and place it in a round-bottom flask, add alkaline methanol-DMF solution, reflux at 55-65° C. for 60 minutes, add citric acid, bismuth salt and copper salt to the treated mixture, continue to stir at 55-65° C. to fully mix, transfer the mixture to a polytetrafluoroethylene reactor, heat at 110-130° C. for reaction for 24 hours, slowly cool to room temperature after the reaction is completed, and dry to obtain citric acid-Cu-Bi complex modified bamboo powder;
[0010] The mass ratio of the bamboo powder to citric acid is 4-5:1, the molar ratio of citric acid to bismuth salt is 1:1.1-1.3, and the molar ratio of citric acid to copper salt is 1:1-2; the particle size of the bamboo powder is 160-200 mesh;
[0011] 3. Preparation of bamboo charcoal catalyst
[0012] The citric acid-Cu-Bi complex modified bamboo powder was calcined in a nitrogen atmosphere at 500-600°C in a tubular furnace for 1-3 hours, and then slowly cooled to room temperature at a rate of 5°C / min. The reaction product was calcined at 300-350°C under aerobic conditions for 1-2 hours to regulate the valence states of metallic copper and bismuth. After cooling, a bamboo charcoal catalyst doped with nano-Cu2O, nano-CuO, nano-Bi2O3, and nano-CuBi2O4 crystal phases in a graphite phase carbon (C) matrix was obtained.
[0013] The bamboo charcoal catalyst doped with Cu2O, CuO, Bi2O3, and CuBi2O4 nanocrystals prepared by the above method was applied to the degradation of ofloxacin antibiotics. The results showed that the bamboo charcoal catalyst prepared by the present invention could completely degrade ofloxacin in 25 minutes.
[0014] Advantages and technical effects of the present invention:
[0015] 1. The present invention uses bamboo powder as a raw material, first prepares a citric acid-Cu-Bi complex modified bamboo powder precursor, and then uses a two-step treatment of high-temperature calcination under nitrogen protection and aerobic calcination in a muffle furnace to embed and disperse four nano-active components in the graphite structure of bamboo charcoal to form a copper-bismuth bimetallic doped bamboo charcoal catalyst with a stable structure. Cu2O, CuO, Bi2O3, and CuBi2O4 doped in the bamboo charcoal catalyst are all nano-scale active catalytic centers;
[0016] 2. The copper-bismuth bimetallic doped bamboo charcoal catalyst prepared by the present invention can activate potassium permonosulfate in the application of degrading antibiotics, and can completely oxidize and degrade ofloxacin in 25 minutes; the catalyst of the present invention has a strong adsorption capacity for ofloxacin, high catalytic activity, and a short degradation time; the present invention provides a new way for the complete oxidation degradation of antibiotics in sewage. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the scanning electron microscope (SEM) image of bamboo charcoal catalyst Cu / Bi-BC;
[0018] Figure 2 This is the X-ray energy dispersive spectrum (EDS) diagram of bamboo charcoal catalyst Cu / Bi-BC;
[0019] Figure 3 This is the X-ray diffraction pattern of bamboo charcoal catalyst Cu / Bi-BC;
[0020] Figure 4 This is the X-ray photoelectron spectrum of bamboo charcoal catalyst Cu / Bi-BC, where Figure a is the full spectrum and Figure b is the C 1s spectrum;
[0021] Figure 5 X-ray photoelectron spectra of bamboo charcoal catalyst Cu / Bi-BC, where a is the O 1s XPS spectrum and b is the Cu2p spectrum;
[0022] Figure 6 The X-ray photoelectron spectrum of bamboo charcoal catalyst Cu / Bi-BC, where a is the Auger spectrum of Cu element and b is the 4f spectrum of Bi;
[0023] Figure 7 The absorbance of ofloxacin solution in the presence of bamboo charcoal catalyst changes with catalytic degradation time;
[0024] Figure 8 The sulfate radicals (SO4• - ) (left) and singlet oxygen ( 1 Electron paramagnetic resonance spectrum of O2) (right). DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the contents should not be regarded as limiting the present invention. The methods in the present embodiments are operated according to conventional methods unless otherwise specified, and the reagents used are conventional reagents or reagents prepared according to conventional methods unless otherwise specified.
[0026] Example 1: Preparation of copper-bismuth bimetallic doped bamboo charcoal catalyst
[0027] 1. Measure 40 mL of methanol and 20 mL of DMF in a 100 mL beaker, mix well, add 24 mg of NaOH, and stir magnetically for 15 min to completely dissolve the NaOH to prepare an alkaline methanol-DMF solution;
[0028] 2. Weigh 1g of bamboo powder of giant dragon bamboo (160-200 mesh) into a round-bottom flask, add 15mL of alkaline methanol-DMF solution, heat and reflux in an oil bath at 60℃ for 60min, add 0.2g of citric acid (1mmol), 0.60g of Bi(NO3)3·5H2O (1.2mmol), and 0.484g of Cu(NO3)2·3H2O (2mmol) to the treated mixture, continue to stir magnetically at 60℃ for 30min, after all components are fully mixed, transfer the mixture to a 100mL polytetrafluoroethylene reactor (with a stainless steel shell), heat and react at 120℃ for 24h, slowly cool to room temperature after the reaction is completed, and dry the reaction product in a 50℃ drying oven to obtain light green citric acid-Cu-Bi complex modified bamboo powder;
[0029] 3. Put the dried citric acid-Cu-Bi complex modified bamboo powder into a quartz crucible, and heat it to 500°C at a rate of 5°C / min in a tube furnace under nitrogen protection and keep it warm for 3 hours, and slowly cool it to room temperature at a rate of 5°C / min to obtain a black powdery copper-bismuth co-doped bamboo charcoal precursor;
[0030] 4. Place the copper-bismuth co-doped bamboo charcoal precursor in a muffle furnace, heat it to 300°C at a rate of 5°C / min, and keep it warm for 1.5h under aerobic conditions. 0 and Bi 0 A slow and complex oxidation reaction occurs, generating four crystal phases of nano Cu2O, CuO, Bi2O3, and CuBi2O4 in the graphite structure of bamboo charcoal; after cooling to room temperature, bamboo charcoal catalyst Cu / Bi-BC doped with Cu2O, CuO, Bi2O3, and CuBi2O4 crystal phases is obtained;
[0031] The microstructure of bamboo charcoal catalyst Cu / Bi-BC was obtained by field emission scanning electron microscopy (SEM). Figure 1As shown in the figure, it can be clearly seen that the catalyst Cu / Bi-BC is composed of many irregular block structures with a rough surface and many pore structures. The surface of these block structures has many Cu particles with a size of about 20 nm. X O (copper oxide and cuprous oxide) small particles aggregated, proving that Cu X O successfully doped.
[0032] The surface element composition and distribution of bamboo charcoal catalyst Cu / Bi-BC sample were characterized by X-ray energy dispersive spectroscopy (EDS). Figure 2 As shown, it can be seen from the total energy spectrum that the sample contains four elements, C, O, Cu and Bi, with atomic proportions of 39.2%, 40.5%, 10.9% and 9.5%, respectively. The proportions of Cu and Bi are also consistent with the prepared sample ratio. In addition, the element surface scan shows the uniform distribution of C, O, Cu and Bi elements, indicating that the Cu and Bi catalytic active centers have been successfully dispersed into the bamboo charcoal matrix.
[0033] X-ray diffraction (XRD) analysis shows that the diffraction peaks of Cu / Bi-BC are consistent with the diffraction patterns of CuBi2O4 (PDF#97-001-2104) and Bi2O3 (PDF#97-019-0461), among which the strong peaks at 20.88°, 28.01° and 46.7° are attributed to the (200), (211) and (141) crystal planes of CuBi2O4, respectively. In addition, the diffraction peaks of Bi2O3 / CuBi2O4 overlap with each other, but the main characteristic peaks do not change, indicating that Bi2O3 and CuBi2O4 coexist. Diffraction peaks at 36.45°, 42.34°, 35.56° and 38.72° were also observed in the sample, which were attributed to the (111)(200) crystal plane of Cu2O (PDF#97-018-0846) and the (-111)(111) crystal plane of CuO (PDF#97-008-7123) ( Figure 3 ), X-ray diffraction analysis showed that four crystal phases of Cu2O / CuO / Bi2O3 / CuBi2O4 have been successfully generated in the graphite phase structure of bamboo charcoal.
[0034] X-ray photoelectron spectroscopy (XPS) was used to determine the state and chemical composition of the elements in the catalyst. Figure 4-6 is the XPS spectrum of Cu / Bi-BC, Figure 4 a is the full XPS spectrum of the Cu / Bi-BC sample, showing that the main elements in the Cu / Bi-BC catalyst are C, O, Cu and Bi. In the C 1s XPS spectrum ( Figure 4 b) The binding energy peaks at 286.4eV and 288.8eV are attributed to the CO and C=O bonds. Figure 5 In a, the O 1s XPS spectrum can be convoluted into three peaks at 529.93 eV, 531.96 eV, and 533.47 eV, of which 529.93 eV can correspond to lattice oxygen (Bi-O bond), while 531.96 eV and 533.47 eV are attributed to C=O and CO groups. Figure 5 b, 6a are Cu 2p XPS fine spectrum and Auger spectrum. The characteristic peaks at 933.45 eV and 953.08 eV are attributed to Cu 0 / Cu + , while Cu appeared at 934.56eV and 954.41eV 2+ The characteristic peaks of Cu appear at 942.44eV and 962.58eV. 2+ Satellite peak. The Auger spectrum (LMM) of Cu element further proves that the valence state of Cu on the catalyst surface is Cu + and Cu 2+ .from Figure 6 As can be seen in b, the peaks of the Bi 4f XPS fine spectrum centered at 158.87 eV and 164.19 eV correspond to the Bi 4f 7 / 2 and Bi 4f 5 / 2 The characteristic peak of the inner electron indicates that all Bi elements in the sample are Bi 3+ exists in the form of.
[0035] Example 2: Experiment on the degradation of ofloxacin by bamboo charcoal catalyst Cu / Bi-BC
[0036] Add 50 mL of 20 mg / L ofloxacin solution to the reaction beaker, turn on the circulating condensed water to keep the reaction liquid in the beaker reacting at a constant temperature. Then add 20 mg of the catalyst Cu / Bi-BC, and stir magnetically for 15 minutes to allow ofloxacin to reach adsorption-desorption equilibrium on the catalyst surface. Thereafter, add 0.1 mmol / L potassium permonosulfate (PMS) as an oxidant to the above system to start the degradation reaction. During the reaction, take out 2 mL of the supernatant from the reaction system every 5 min, filter with a 0.22 μm microfiltration syringe to remove the catalyst suspended in the aqueous solution, and continuously scan and test the absorption spectrum of ofloxacin with a UV-visible spectrophotometer. Ofloxacin has two characteristic absorption peaks, located at 289 nm and 330 nm respectively; the degradation rate of ofloxacin is calculated based on the absorbance value at the maximum absorption wavelength of 289 nm. The changes in the UV-visible absorption spectrum of ofloxacin with reaction time t are shown in Figure 7 It can be found that as the catalytic reaction proceeds, the absorption spectrum of ofloxacin rapidly weakens, indicating that the concentration decreases rapidly. The degradation rate of ofloxacin is expressed by DE:
[0037] According to the formula DE = (1-C t / C0)×100%, where C t is the concentration value after degradation time t, C0 is the concentration value of ofloxacin at t = 0; the concentration value of ofloxacin here can be replaced by the absorbance value at 289 nm.
[0038] The experimental results show that, first, ofloxacin is rapidly adsorbed on the catalyst surface, reaching adsorption equilibrium within 15 minutes, and the absorbance decreases from 0.511 to 0.252. Afterwards, potassium permonosulfate is added as an oxidant to start the catalytic degradation reaction. The catalyst Cu / Bi-BC can effectively activate potassium permonosulfate, and 98.7% of the ofloxacin antibiotic is detected to be oxidized and degraded at 25 minutes, which is close to complete oxidative degradation.
[0039] At the same time, a comparative experiment was set up, and the results showed that with the same reaction time, using a single Bi2O3 as a catalyst could not catalytically degrade ofloxacin; using Cu2O as a catalyst, only 23% of the ofloxacin antibiotic was oxidatively degraded; using unmetal-modified bamboo charcoal (BC) as a catalyst, only 49% of the ofloxacin was adsorbed by the catalyst, and then it could no longer be degraded.
[0040] In addition, we detected the presence of sulfate radicals (SO4• - ) and singlet oxygen ( 1 O2) two active species, proving that the Cu / Bi-BC / PMS catalytic system can be - and 1 O2 oxidizes and degrades ofloxacin, SO4• - and 1 The electron paramagnetic resonance spectrum of O2 is shown in Figure 8 .
Claims
1. A method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation, characterized in that: The bamboo powder is placed in an alkaline methanol-DMF solution and refluxed at 55-65°C for 60 minutes; citric acid, bismuth salt and copper salt are added to the treated mixture, and the mixture is stirred and mixed at 55-65°C until uniform, and then the mixture is transferred to a reactor, heated at 110-130°C for 24 hours, and slowly cooled to room temperature after the reaction is completed, and dried to obtain citric acid-Cu-Bi complex modified bamboo powder; the citric acid-Cu-Bi complex modified bamboo powder is calcined at 500-600°C for 1-3 hours in a nitrogen atmosphere, and then slowly cooled to room temperature at a rate of 5°C / min; the reaction product is then calcined at 300-350°C under aerobic conditions for 1-2 hours, and after cooling, a bamboo charcoal catalyst in which four crystal phases of nano-Cu2O, nano-CuO, nano-Bi2O3 and nano-CuBi2O4 are embedded in a graphite layer is obtained.
2. The method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation according to claim 1, characterized in that: The alkaline methanol-DMF solution is prepared by adding NaOH to a methanol-DMF mixture to obtain a solution with a NaOH mass volume concentration of 35-45%, wherein the methanol-DMF mixture is prepared by mixing methanol and DMF in a volume ratio of 2:
1.
3. The method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation according to claim 1, characterized in that: The mass ratio of bamboo powder to citric acid is 4-5:1, the molar ratio of citric acid to bismuth salt is 1:1.1-1.3, and the molar ratio of citric acid to copper salt is 1:1-2.
4. The method for preparing copper and bismuth co-doped bamboo charcoal catalyst by citric acid complexation according to claim 1, characterized in that: The particle size of bamboo powder is 160-200 mesh.
5. Use of the copper-bismuth co-doped bamboo charcoal catalyst prepared by the method for preparing the copper-bismuth co-doped bamboo charcoal catalyst by citric acid complexation according to any one of claims 1 to 4 in the degradation of ofloxacin.
Citation Information
Patent Citations
Preparation method and application of pine needle biochar flower-shaped BiOCl-loaded composite photocatalyst
CN105664980A
Preparing method and application of bamboo-stem-carbon-sphere-protonated-g-C3N4-wrapped composite catalyst
CN108043445A